Serum basement membrane and type III procollagen-related antigens in primary biliary cirrhosis - Niemelä, O; Risteli, L; Sotaniemi, E A; Stenbäck, F; Risteli, J (Journal of hepatology, 1988)
A characteristic histological lesion in early primary biliary cirrhosis (PBC) is disruption of the basement membrane around small bile ducts, which at later stages of the disease is followed by fibrosis. To assess the significance of serum basement membrane- and type III procollagen-related antigens in reflecting such processes, we have measured radioimmunologically the concentrations of serum laminin, type IV collagen and the aminoterminal propeptide of type III procollagen in 22 patients with PBC, classified into four stages according to liver histology. The mean laminin concentration in PBC patients was twice that of the healthy control subjects. Increased concentrations were observed in all patients with stage III or IV of the disease and also in 60% (6/10) of the patients, with early stages (I or II). Elevated serum type IV collagen concentrations were found only in four patients, all in the late, fibrotic stages of the disease. The basement membrane protein changes in serum were in accordance with immunohistochemical findings obtained with the antibodies against these proteins. Neither of these serum parameters emerged, however, as a significant predictive factor for survival. The changes in serum aminoterminal propeptide of type III procollagen resembled those in laminin P1. Moreover, the propeptide was also significant as a predictive factor for survival.